GRANULAR AQUIFER SYSTEM OF WEST CHALKIDIKI AREA, REGION OF CENTRAL MACEDONIA, NORTHERN GREECE - Veranis, N.; Nimfopoulos, M.; Christidis, C.; Chrysafi, A. (Bulletin of the Geological Society of Greece, 2016)
The granular aquifer system of the western Chalkidiki peninsula covers an area of 667 Km2 occupying Neogene and Quaternary sediments. The present study deals with the hydrogeological and hydrogeochemical characterization of the granular aquifer system for the purposes of efficient utilization and management of groundwater resources. It is a multilayered formation, composed of unconsolidated to semi-consolidated sands, gravels, conglomerates, sandstones and marly limestones with intercalated impermeable to semi-permeable beds of clays, marls or mixed with pebbles and sands. The aquifer system is characterized by medium to moderate hydrocapacity and the pumped groundwater consumptions are 74*106 m3/yr. Piezometric studies carried out in the period of 2003-14, conclude that the piezometric surface decline is located in the S and SE parts of the aquifer system, while in the rest Central and NW parts there is a noticeable rising of the groundwater table. Groundwater is generally characterized by a good quality; however, groundwaters of the broader Triglia area, have excessively high contents of As (10 to 3400 μgr/l) and B (1.5 to 4.0 mg/l). Other natural pollutants are Fe and Mn. Salinization and high values of nitrate are mainly detected in water boreholes of Moudania-Portaria, Akrotiri-Epanomi and Agelochori areas.